Discovery of an Antibiotic-Related Small Protein of Biocontrol Strain Pseudomonas sp. Os17 by a Genome-Mining Strategy - Takeuchi, Kasumi; Tsuchiya, Wataru; Fujimoto, Zui; Yamada, Kosumi; Someya, Nobutaka; Yamazaki, Toshimasa (Frontiers in Microbiology, 2020)
Many root-colonizing Pseudomonas spp. exhibiting biocontrol activities produce a wide range of secondary metabolites that exert antibiotic effects against other microbes, nematodes, and insects in the rhizosphere. The expression of these secondary metabolites depends on the Gac/Rsm signal transduction pathway. Based on the findings of a previous genomic study on newly isolated biocontrol pseudomonad strains, we herein investigated the novel gene cluster OS3, which consists of four genes (Os1348–Os1351) that are located upstream of putative efflux transporter genes (Os1352–Os1355). Os1348 was predicted to encode an 85-aa small precursor protein, the expression of which was under the control of GacA, and an X-ray structural analysis suggested that the Os1348 protein formed a dimer. The mutational loss of the Os1348 gene decreased the antibiotic activity of Pseudomonas sp. Os17 without changing its growth rate. The Os1349–1351 genes were predicted to be involved in post-translational modifications. Intracellular levels of the Os1348 protein in the deficient mutant of each gene differed from that in wild-type cells. These results suggest that Os1348 is involved in antibiotic activity and that the structure or expression of this protein is under the control of downstream gene products.